Nothing Academic green space for development campus: student Perseption and ekspetation - Rodhiyah, Afifatur (Maliki Interdisciplinary Journal, 2024)
Student World is inseparable from the word assignment. Assignments have become daily food for students. Most students choose to study individually because they feel calmer and more comfortable. However, what if students know what it’s like to study in groups. Studying in groups is actually more comfortable if the place for studying in groups is fun. An open green place allows it to increase enthusiasm for learning and foster a sense of fun while studying. In this study, we want to discuss green open learning spaces on campus in terms of student perceptions and expectations. The research method used is the quantitative method by distributing questionnaires to students from various campuses and accommodating their perceptions regarding the expected study space. The results of this study are that green open spaces are a hope for students to carry out learning activities, especially in groups. Studying in green open spaces can eliminate boredom and increase enthusiasm for student learning. From these student perceptions, it was concluded that green open spaces are suitable for student learning activities. The construction of green open spaces has a positive impact on students’ mental health in carrying out assignments. So, it is recommended to build green open spaces on campus to support student learning activities.